Caracterização hidrogeoquímica e qualidade da água de poços tubulares em aldeias indígenas na região da Amazônia Central - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This paper presents results obtained from the investigation of the hydrogeochemical characteristics and the groundwater quality of the Alter do Chão Aquifer referring to five tubular wells located in indigenous villages of two municipalities of Central Amazonia, which are supported by siliciclastic rocks of Alter geological formations (Cretaceous) and Novo Remanso (Neogene) covered by quaternary fluvial deposits. Physical, physical-chemical, ionic, microbiological, organoleptic and hydrogeological parameters were analyzed. The values of air and water temperature remained relatively homogeneous, varying between 24 ° C and 32.5 °C and 26.6 °C and 28.8 °C, respectively. The pH results show acidic water ranging from 4.67 to 6.58; The electrical conductivity in all studied periods showed values varying between 17.67 and 106.3 (μS /cm), indicating weakly mineralized waters. The results of substances posing a health risk (aluminum, arsenic, barium, cadmium, copper, chromium, fluoride, nitrate, nitrite, nickel and zinc) are mostly below the detection limit of the equipment and the values detected for barium, cadmium, copper, nitrate, nitrite and zinc are below the maximum values allowed by current legislation. All the analytical results obtained from these waters in the seasonal and transitional periods were compared with the potability standards established in the current legislation and are suitable for human consumption, with no evidence of contaminants. The poor mineralization of the analyzed waters reflects the low concentrations of the dissolved constituents, because the water percolates poor soils, typical of the strong weathering to which the region is submitted. The use of the Piper diagram showed a varied hydrochemical behavior, resulting in a varied classification in four wells. In relation to the hydrogeological aspect, in general, the shallower wells (TU, NE and MK) with depths ranging from 46 to 50 meters presented the lowest and best values of static and dynamic levels, indicating more areas of recharge entries, with a higher score for MK in all periods studied.
Keywords: Água subterrânea; Hidrogeoquímica; Potabilidade; Aldeias indígenas; Groundwater; Hydrogeochemistry; Potability; Indigenous Villages; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS